SELF SOCIALIZATION PROCESS OF GENERATION Z BASED ON TYPE ONLINE GAME AT SMK NEGERI 4 KOTA PROBOLINGGO - Albertus Endra Budi Setiawan (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2019)
Cyber interactions have replaced conventional face-to-face interactions in the socialization of daily life. This situation is often encountered in generation Z, born in 1995-2011. The interaction of cyberspace in question is an online game. There were 8 students interviewed at SMK 4 Negeri Probolinggo City. 4 students who regularly play online games and 4 students who do not regularly play online games. The result is self-discipline, confidence in groups and communicating with teachers, understanding self-potential, being active in developing strategies so that achievement in the classroom becomes a positive result when students play online games.